Antilisterial action of Pediococcus acidilactici AA5a in pork sausage fermentation - Marilao, Catherine G.; Calapardo, Marilou R.; Ciron, Christian E.; Elegado, Francisco B. (2007)
Pediococcus acidilactici AA5a, a bacteriocinogenic lactic acid bacterium isolated from fermented rice-fish mixture (burong isda), was used as inoculum in pork sausage fermentation, and assessed for its antimicrobial activity against listeria. Inoculum level of 8 Log CFUg-1 of P. acidilactici AA5a in beaker sausage fermentation was found to effectively inhibit the growth of putative listeria colonies (enumerated through black discoloration in the listeria-selective PALCAM agar medium). The optimum inhibitory activity occurred during the 12-20th hour of fermentation. But after such time, putative listeria colonies inherent in the meat mixture started to reappear. Using traditional sausage preparation (pork mixed with spices stuffed in intestinal casing and air dried for 1 h) and inoculation with similar 8 Log CFUg-1 of P. acidilactici AA5a inhibited the growth of putative Listeria colonies inherent in the meat mixture. However, the growth of spiked L. grayi CM904 after 16 h was not significantly inhibited by P. acidilactici AA5a inoculation even with the presence of nitrite. Putative listeria representing L. grayi CM904 and inherent listerial contaminants in the sausage mixture was still way above the maximum allowed concentration of 2 log CFUg-1 setby the International Commission on Microbiological Specifications for Foods (ICMSF) for L. monocytogenes.
Keywords: Lactic acid bacteria; Sausages